Towards an understanding of big points in tennis: perspectives of coaches, professional players, and junior players - Meffert, D.; Breuer, J.; Ohlendorf, L.; Born, P.; Grambow, R.; Vogt, T. (Journal of Physical Education and Sport, 2021)
Tennis is a game with different mental challenges during a competitive match. With this, the importance of some points over others is well-accepted; so-called 'big points` may have a decisive character on the outcome of a tennis match.However, even if the term itself is used regularly by players, coaches and commentators, a definition of a `big point` is still required. Objective: The present study aimed to elucidate the wider understanding,ideally an approach for a definition, of big points in tennis. Methods:For this purpose, a number of tennis experts (licensed coaches, professional players, junior player and "others"; n= 174) participated in an online survey, classifying pre-categorized potential big points in tennis (i.e., the match situation and score from a serving- or returning perspective). For this, the participants of the survey answered standardized closed questions, one multiple choice-question and one opened question. Results: Findings reveal a substantial agreement about the existence of big points (97.30%) and a general consensus about the classification of points as big points between professional players and junior players. However, other than a clear definition of a big point, in particular coaches and players show different understandings. Thus, an additional summary of self-reported understandings on the term 'big point' itself supports a more general defining approach; however, the subjective understanding on the importance of a point remains to be decisive for its classification as big point. Conclusions: Big points exist in professional tennis. The performance of these decisive moments is one key factor for success in professional tennis and regular mental training is recommended to keep or even raise the level of performance in these moments.